2018
DOI: 10.1016/j.ecoenv.2018.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of the novel chiral insecticide IPP and its biodegradation intermediate in nematode Caenorhabditis elegans

Abstract: Caenorhabditis elegans, a kind of model organism, was used to investigate biodegradation pathway of IPP and M1 in nematodes, in vivo toxicity from IPP and M1 and the possible underlying molecular mechanism. The results showed that both IPP and M1 could decrease lifespan, locomotion behavior, reproductive ability and AChE activity. During IPP biodegradation process, three intermediates (M1-M3) were monitored and identified. Based on the identified metabolites and their biodegradation courses, a possible biodegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The head thrashing frequency and body bent frequency were recorded at 1, 3, 6, and 12 h post-treatment assisted by a dissecting microscope (45×). The head thrashing and body bend frequency were recorded according to a previous method [51]. The MM liquid medium without microorganisms and 6-oxychitin served as a control.…”
Section: Anti-nematode Assay 471 Effect On J2s Locomotion Behaviourmentioning
confidence: 99%
“…The head thrashing frequency and body bent frequency were recorded at 1, 3, 6, and 12 h post-treatment assisted by a dissecting microscope (45×). The head thrashing and body bend frequency were recorded according to a previous method [51]. The MM liquid medium without microorganisms and 6-oxychitin served as a control.…”
Section: Anti-nematode Assay 471 Effect On J2s Locomotion Behaviourmentioning
confidence: 99%
“…The most complete publications, reported on 26 out of 30 criteria [ 30 ] that we formulated, the most incomplete reported only 15 of 30 criteria [ 31 , 32 ] ( Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…43,44 Furthermore, pesticides including paichongding and spirotramat interrupted life cycle and shortened lifespan of nematodes. 45,46 These findings implied that exposure to environmental xenobiotics such as fluopimomide adversely affected survival of C. elegans. An increase in ROS accumulation indicated that the nematodes were under oxidative stress, which was considered to be an important factor leading to aging.…”
Section: Exposure To Fluopimomide At Sublethal Doses Shortened Lifesp...mentioning
confidence: 97%